Getting rights right: implementing 'Martha's Rule' - Graham, M; Hart, J; Hanson, I; Lignou, S; Peter, Y; Parker, M; Sheehan, M (BMJ Publishing Group, 2024)
The UK government has recently committed to adopting a new policy —dubbed ‘Martha’s Rule’— which has been characterized as providing patients the right to rapidly access a second clinical opinion in urgent or contested cases. Support for the rule emerged following the death of Martha Mills in 2021, after doctors failed to admit her to intensive care despite concerns raised by her parents. We argue that framing this issue in terms of patient rights is not productive, and should be avoided. Insofar as the ultimate goal of ‘Martha’s Rule’ is the provision of a clinical service that protects patient safety, an approach that focuses on the obligations of the health system —rather than the individual rights of patients— will better serve this goal. We outline an alternative approach that situates rapid clinical review as part of a suite of services aimed at enhancing and protecting patient care. This approach would make greater progress towards addressing the difficult systemic issues that Martha’s Rule does not, while also better engaging with the constraints of clinical practice.